Implementasi Kebijakan Keterbukaan Informasi Publik : Studi pada Pejabat Pengelola Informasi dan Dokumentasi Kota Serang - Lathifah Chairunnisa; Fikri Habibi; Rethorika Berthanila (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2023)
Implementation of public information disclosure policy in the Public Information and Documentation Office (PPID) of Serang City. Public information disclosure in Indonesia is governed by the Public Information Transparency Act (UU KIP) Number 14 of 2008, and in the PPID of Serang City, it is implemented to fulfill the rights of public officials to carry out their roles transparently. The study adopts a quantitative approach with 70 respondents as the sample, and data is collected through questionnaires. The implementation policy model used is Merilee S. Grindle's model, which includes content of policy and context of policy variables. Data analysis is conducted using multiple linear regression, coefficient of determination, T-test, and F-test. Based on the research results using VOSviewer 1.6.16 software with Scopus database, it was found that there is a significant influence between the content and context of policy variables on the implementation of public information disclosure policy. The content of policy variable plays the most dominant role with an influence rate of 99%, while the context of policy variable has an influence rate of 84.83%.